Contemporary diagnostics and treatment of thorax deformations in children - Bulandra, Andrzej M.; Bohosiewicz, Janusz (Przewodnik Lekarza/Guide for GPs, 2012)
Congenital defects of the thorax are a wide spectrum of deformations. Some defects have only cosmetic importance, however, a large group of them determines vital organs impairment and may be life-threatening. Diagnostics and treatment of congenital thorax defects is a serious challenge. In this article, authors have presented contemporary opinions about aetiology, pathogenesis as well as diagnostics and treatment of congenital thorax deformations in children. Sternal cleft, pectus excavatum, pectus carinatum, Poland and Jeune syndroms have been discussed.